The influence of career path elements, mentoring and career development strategies on women employability in Iran’s tourism industry / Simin Saghafi - Saghafi, Simin (2014)
One of the important criteria in evaluating a country’s development is the attention given towards women’s welfare, development and also recognizing their active and creative powers. In the past three years, Iran’s fifth five-year plan (2011-2015) showed an indication of various amount of barriers for women’s employability such as low level of literacy, low variety for job opportunities and high cost of labor particularly for women. It is worth noting that the booming tourism industry has created vast economic opportunities, creating job prospects for women globally and it is also said to provide better opportunities for women’s participation in the workforce, entrepreneurship and leadership as compared to other sectors of the economy. This study was conducted to examine the influence of career path elements, mentoring and career development strategies towards women employability in the Iran’s tourism industry. A total of 350 questionnaires were distributed to female workers in hotels, travel agencies and tour guide associations in the capital city of Tehran, Iran, with a response rate of 52 percent. Data was analyzed by using various forms of statistical tool such as descriptive analysis, factor analysis, reliability test and multiple regression. Results of multiple regression showed significant influence of career path elements and mentoring towards women’s employability (3 = .46 and 20 (p <.05). Also based on these results, in the presence of career development strategies (P=.34, p<.01), the partial mediation has taken place in the relationship between career path elements and women employability. Meanwhile results for this study supported all hypotheses. The results of this study are able to further bridge the gap found in previous studies in women employability in tourism industry that did not stress on the importance of separating the measurement of career path elements. The findings of present study also have implications for the organizations in Iran’s tourism industry.